STUDI POTENSI TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH “PUTRI CEMPO” SURAKARTA SEBAGAI SUMBER PAKAN SAPI POTONG - Sudiyono Sudiyono; Eka Handayanta (Universitas Sebelas Maret, 2010)
This Research aim to to know the potency from place of exile final garbage Putri Cempo Surakarta as feed source of beef cattle. Research executed during six-month at some locations, there are: 1) TPA Garbage